ETNOMATEMATIKA CONGKLAK DALAM PEMBELAJARAN OPERASI BILANGAN DI SMKN 13 KABUPATEN TANGERANG - Adkhiyah Adkhiyah; Asep Muhyidin; Ujang Jamaludin; Aan Asphianto (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the mathematical concepts embedded in the traditional Congklak game and to describe its application in number operations learning through an ethnomathematics approach. The study highlights how local cultural practices can be used as meaningful contexts for strengthening students’ mathematical understanding. Methods: This research employed a qualitative exploratory descriptive method. Data were collected through observation of Congklak play activities, documentation, and literature study. The data were analyzed using the stages of data reduction, data display, and conclusion drawing to identify mathematical concepts and their relevance to classroom learning. Results: The findings show that Congklak contains various mathematical concepts, including number operations, one-to-one correspondence, numerical patterns, geometry, symmetry, logical reasoning, and problem-solving strategies. The process of distributing seeds from one hole to another represents addition, subtraction, multiplication, and division in a concrete and culturally familiar context. Congklak also supports contextual learning because students can connect abstract mathematical symbols with direct manipulation of objects and explain the meaning of each calculation through play-based activities.